Maximizing VA Benefits for Survivors of Military Sexual Trauma: A Practical Guide for Survivors and Their Advocates - Seamone, Evan R.; Traskey, David M. (Columbia Journal of Gender and Law, 2014)
Military Sexual Trauma (MST) is an imprecise term that basically relates to “sexual assault or repeated, unsolicited, threatening acts of sexual harassment that occurs during military service.” Despite a variety of definitions for “sexual assault” and “sexual trauma” (e.g., some including verbal harassment), and differences in populations sampled (e.g., active duty members versus treatment-seeking veterans), estimates consistently indicate that that just over 20% of females and 1% of males are sexually assaulted in a physical manner during their service. The numbers rise substantially to 20% of males and 70% of females in studies where verbal trauma is included in the definition. Importantly, the term MST was “created to capture the different forms of sexual maltreatment reported by military personnel.” Thus, MST “is not a syndrome, diagnosis, or construct associated with clear treatment indications.” Instead, it represents a type of stressor that can result in such maladies. Recent and renewed interest in the MST epidemic has resulted in legislative proposals to revamp the entire military justice system to hold perpetrators accountable and encourage survivors to report their abuse, as well as ongoing efforts within the Department of Veterans Affairs (VA) to accommodate MST survivors’ needs for medical treatment and empathic, bias-free benefits adjudication. However, commentators emphasize the likelihood that pervasive systemic oversights within the VA and the Department of Defense (DoD) will result in continued incidences of MST among active duty service members and the erroneous denial of VA benefits to MST survivors who, in many cases, desperately need and rightfully deserve them.